Analisis Konten Instagram @alazharcenterpare dalam Pembelajaran Bahasa Arab Online - Rahmawati, Siti Uriana; Aisyah, Siti Nurul; Mufidza, Shafira; Umbar, Kisno (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2024)
The development of science and technology demands educators to continually enhance innovation and creativity in teaching and learning activities. Proficiency in language, particularly Arabic, is crucial to facilitate communication, understand the Quran and Hadith, and broaden perspectives. The learning of the Arabic language can be facilitated through the use of applications and platforms available over time. An analysis of the content on the Instagram account @alazharcenterpare was conducted to identify various features and content that can be utilized as a learning medium in the digital era. Using a qualitative descriptive method, this research will illustrate Instagram as one of the widely used applications for learning media due to its various attractive features such as stories, reels, and feeds. The stories feature is a suitable choice for conducting quizzes, polls, and Q&A sessions to assess the extent of students' proficiency in understanding the Arabic language. Thus, this research indicates that Instagram, with its diverse and contemporary features, can enhance the enthusiasm and motivation of individuals in learning the Arabic language.